Penggunaan Marka DNA dalam Seleksi Induk Ikan Kerapu Macan (Epinephelus fuscoguttatus) yang Tahan Terhadap Bakteri Vibrio alginolyticus - Triana, St Hidayah; Gani, Mahir S; Tassakka, Asmi Citra Malina A.R; Hamka, Hamka (Torani Journal of Fisheries and Marine Science, 2014)
The objective of the present study was to use selected RAPD markers (Primer UBC-122 and YNZ-22) in parental selection to the bacterial Vibrio alginolyticus resistance in Tiger groupers (Epinephelus fuscoguttatus).  Eighteen fish parent samples were challenged with Vibrio alginolyticus and parental selection was examined by a PCR-RAPD method.   The results showed that from 18 fish samples, primer YNZ-22 generated 18 fragments while primer UBC-122 generated 8 fragments only (KHP, KB, HB, PB, MKH, MH, K and MK).  In addition, the average number of fragments from each samples generated from primer-YNZ was higher (3,2) than from UBC-122 (2,3). This indicates that primer YNZ-22 is better than primer UBC-122 to use in parental selection to the Vibrio alginolyticus resistance in Tiger groupers.  From the parental selection, five fish parents (KHP, PB, MH, K and  MK) were selected for their high resistance to the bacterial Vibrio alginolyticus.